PARENTING BAGI ORANG TUA MUDA DI PUSAT PEMBELAJARAN KELUARGA SURABAYA PERSPEKTIF ABDULLAH NASHIH `ULWAN - ., `Azmatul Husniyah (Program Studi Hukum Keluarga Islam Fakultas Syariah dan Hukum, 2019)
In this information and technology era, families face many challenges, especially in terms of childcare. The many social issues related to the family, especially the role of parents, make government institutions take the initiative to build family resilience by providing parents with knowledge about parenting. This article intends to highlight parenting activities for young parents held by the Surabaya City Government through the Puspaga (Family Learning Center) program. This program is intended to increase the knowledge of young parents about parenting towards children and make them aware of the importance of knowledge about parenting as a provision to foster harmonious families. Data was collected using interview techniques with participants and Puspaga administrators and documentation techniques. To assess this practice, the author uses child education theory according to Abdulloh Nashih 'Ulwa who emphasizes education in the fields of faith, morals, physical, psychological, resourceful, and social. The parenting program for young parents held by Puspaga is compatible with the concepts of Islamic education according to Abdullah Nashih 'Ulwa.